Vaping illusions: The hidden risks of E-cigarette use among young Filipinos and adolescents in Latin America - John Patrick C. Toledo (International Journal of Cardiology. Cardiovascular Risk and Prevention)
The study ''E-cigarette use among adolescents in Latin America'' reveals a high prevalence of e-cigarette use among teenagers, with a pooled mean of 18.9 %. This highlights the misconception that e-cigarettes are safer than traditional smoking and calls for focused public health initiatives to combat this growing problem. The study aims to examine the prevalence of e-cigarette use among Latin American teenagers, identify contributing factors, and guide public health initiatives to reduce the hazards associated with vaping. Its methodology comprises the following steps: first, a comprehensive assessment of the body of research on teen e-cigarette use was carried out; second, information on prevalence rates and related variables from multiple studies was gathered. Finally, the pooled mean prevalence was computed to give a bigger picture of the problem. The findings suggest that e-cigarettes, particularly for minors, may prolong nicotine dependency without providing a true cessation pathway. Social and cultural factors also complicate understanding how young Filipinos vape. The study underscores the need for well-informed public health initiatives to reduce the dangers of teen vaping.